Association between multimorbidity and capacity impairment in the adult population of Chile: findings of the National Health Survey 2016–2017 - Pamela Serón; Maria J Oliveros; Raúl Valenzuela-Suazo; Camilo Morales; Constanza Ulloa; Álvaro Sanhueza; Ximena Neculhueque (BMJ Open, 2025)
Objective This study aims to assess the association of multimorbidity with capacity impairment in the Chilean population.Design Cross-sectional study.Setting We analysed data from the National Health Survey performed in Chile in 2016 and 2017.Participants Persons aged 15 years and over were selected using a random, stratified and multistage sampling by clusters in all 15 geographical regions of the country.Primary and secondary outcomes We consider the WHO’s definition of multimorbidity as the coexistence of two or more chronic conditions in the same person. For capacity impairment, the survey included 24 items in eight dimensions that represent functioning as a reflection of the overall health experience perceived by an individual with a health condition and interacting with the environment.Results The 2016–2017 ENS (Encuesta Nacional de Salud) included 6233 participants (mean age 48.9±19.3, and 62% women). There is an association between impairment of capacity and being a woman (OR=1.62; 95% CI 1.37 to 1.92) and between being under 45 years old and conserved capacity (OR=0.8, 95% CI 0.64 to 0.99). The predictive model determined that women classified with five or more chronic conditions of 80 years and over and with less than 8 years of formal education reach the highest probability of having any impairment of capacity.Conclusion Multimorbidity is associated with impaired capacity in the adult population in Chile, and these public health problems are present at early ages and have a greater impact on women.